Perancangan Inventory System Hira Batik Menggunakan Aplikasi Microsoft Access - Agustin, Isnaini Nuzula; Lukito, Ivander (Madani: Jurnal Pengabdian Masyarakat dan Kewirausahaan, 2024)
Hira Batik is an SME (Small and Medium Enterprise) in Batam City specializing in batik fashion which faces inventory management challenges due to the absence of a system to record incoming and sold products. This lack of documentation makes it difficult to track inventory levels, potentially leading to errors in stock management. To address this issue, the author has designed an inventory system using the Microsoft Access application. The data collection approach involves direct interviews with the SME to understand inventory management processes, challenges faced, and system requirements. Additionally, secondary data techniques are utilized to gain further insights into best practices in inventory management. The proposed system aims to assist Hira Batik in monitoring, recording, and managing inventory more efficiently and accurately. The results for Hira Batik show a significant change in warehouse checks, now utilizing an inventory system designed to make a significant contribution and facilitate the recording of transaction data and transaction history.